Audit Committee Impact on Corporate Profitability in Oman Companies: an Auditing and Management Accounting Perspective - Alabdullah, Tariq Tawfeeq Yousif; Ahmed, Essia Ries (Universitas Muhammadiyah Surakarta, 2020)
This work investigates the impact of audit committees’ features as predictor variables of corporate profitability with a sample of firms belong to non-financial sector in Muscat Securities Market (MSM). This work analyzed cross sectional data for 60 non-financial firms. It used annual reports for the year of 2019 to analyze the impact of audit committees’ features on corporate profitability. The present work tested its hypotheses and utilized its variables via utilizing the Smart-PLS for data analysis. The findings revealed that a positive association between all the predictors and dependent variables are exist among the whole variables; audit committee, audit Independence, meeting of audit committee, and corporate profitability measured by management accounting’s indicators represented by ROA and ROE. This work is a new in its kind to be applied in Oman context via examining the relation between its predictors of audit committees’ features towards their impact on corporate profitability. The current study presents a theoretical and practical implications as a contribution relevant to practitioners working and academics in areas related to corporate profitability. In that, it furnishes empirical evidence for the policymakers, researchers and other interested parties.